Stakeholder analysis for digital campus development with 5G micro operators - Risto Jurva; Marja Matinmikko-Blue (International Telecommunications Society (ITS), 2019)
Assumingly very few sectors of society can avoid the digital transformation, which has been storming in the recent years. Despite of the digitalization being a global mega trend and an essence to survive in the modern world, it seems that many entities are still struggling in initiating the transformation process. Instead of dabbling alone to realize big changes, many actors have noted the strengths of co-development through ecosystems. A digital university campus where education and research of the highest class are conducted together represents an important arena for digitalization. This paper introduces research conducted to constitute an ecosystem to realize a digital university campus that is built on the latest communications infrastructure. To start the change process, it is consequential to recognize the stakeholders to define the requirements and targets of the transformational evolution. An analysis of the internal and external stakeholders of the digital campus is introduced based on interviews and discussions. Considering the 5G, IoT, MEC and cloud technologies to comprise the fundamental base of digital campus, a key topic in this research is to evaluate the model of operating and developing the digital infrastructure and services. Among the traditional actors of IT Administration and mobile network operator (MNO) a novel approach is introduced by examining the recent research outcome, which defines a local micro operator driven ecosystem to provide services through a local 5G network.
Keywords: 330